Biogeochemical Equilibrium Responses to Maximal Productivity in High Nutrient Low Chlorophyll Regions. Issue 5 (28th April 2022) - Fu, Weiwei; Wang, Wei‐Lei
Abstract: Whether ocean iron fertilization in high nutrient low chlorophyll (HNLC) regions is a practical geoengineering strategy to combat climate warming has been debated because the fate of absorbed carbon by the ocean remains unclear. We use an optimized oceanic biogeochemical inverse model to explore the equilibrium responses to increased productivity in major HNLC regions. We find that an overall downward shift of nutrients and carbon from the surface and intermediate to the deep waters with maximal productivity in the HNLC Southern Ocean (SO), North Pacific (NP) and eastern equatorial Pacific (EP). The efficiency of soft tissue pump is increased by 37.8%, 2.7% and 5.4% in the SO, EP and NP simulation while atmospheric CO2 concentration is drawn down by 45.1, 3.4 and 6.7 ppm, respectively. Meanwhile, global mean oxygen is decreased by 21.1%, 1.3% and 2.4% in the SO, EP and NP simulation, accompanied by an expansion of oxygen minimum zones by 400%, 26% and 63%, respectively. Our study indicates that iron fertilization has the potential to be an effective geoengineering approach to mitigate climate warming but also has a strong impact on the development of ocean hypoxia. Plain Language Summary: Iron fertilization is proposed as a useful geoengineering tool to mitigate climate warming by stimulating phytoplankton growth and enhancing carbon export to deep ocean. However, the fate of the absorbed carbon in high nutrient low chlorophyll (HNLC) regions remains unclear. Here we use a data‐constrained biogeochemical inverse model to explore the long‐term impact of maximal productivity in different HNLC regions on ocean biogeochemistry and atmospheric CO2 . We performed a series of sensitivity tests that solved the new equilibrium states of key biogeochemical variables. Our results show that iron fertilization in all HNLC regions can reduce the atmosphere CO2 by a maximum of 18.7%, demonstrating the usefulness of iron fertilization. However, iron fertilization also produces side effects including the loss of oxygen inventory and the production of powerful greenhouse gases, for example, N2 O. These side effects can offset the efficacy of iron fertilization and have detrimental impact on the ocean ecosystem. Key Points: We use a data‐constrained biogeochemical inverse model to explore the impact of artifical iron fertilization We demonstrate the equilibrium responses to maximal productivity in different high nutrient low chlorophyll regions for ocean nutrients, oxygen and atmospheric CO2 We show that a drawdown of atmospheric CO2 of 52.3 ppm is compensated by ∼19% by the impact of expanded oxygen minimum zones for combating climate warming